Brain activity in struggling readers before intervention relates to future reading gains. (February 2019) - Nugiel, Tehila; Roe, Mary Abbe; Taylor, W. Patrick; Cirino, Paul T.; Vaughn, Sharon R.; Fletcher, Jack M.; Juranek, Jenifer; Church, Jessica A.
Abstract: Neural markers for reading-related changes in response to intervention could inform intervention plans by serving as a potential index of the malleability of the reading network in struggling readers. Of particular interest is the role of brain activation outside the reading network, especially in executive control networks important for reading comprehension. However, it is unclear whether any intervention-related executive control changes in the brain are specific to reading tasks or reflect more domain general changes. Brain changes associated with reading gains over time were compared for a sentence comprehension task as well as for a non-lexical executive control task (a behavioral inhibition task) in upper-elementary struggling readers, and in grade-matched non-struggling readers. Functional MRI scans were conducted before and after 16 weeks of reading intervention. Participants were grouped as improvers and non-improvers based on the consistency and size of post-intervention gains across multiple post-test measures. Engagement of the right fusiform during the reading task, both before and after intervention, was related to gains from remediation. Additionally, pre-intervention activation in regions that are part of the default-mode network (precuneus) and the fronto-parietal network (right posterior middle temporal gyrus) separated improvers and non-improvers from non-struggling readers. None of these differences were observed during the non-lexical inhibitory control task, indicating that the brain changes seen related to intervention outcome in struggling readers were specific to the reading process.